A marine biofouling and anti-corrosion coating material with high mechanical strength
By copolymerizing zwitterionic groups and hydrophobic groups in conductive polymer materials, an amphiphilic conductive polymer coating was prepared, which solved the problems of insufficient anti-fouling stability and insufficient mechanical strength of the existing coating, and achieved Effective protection and corrosion protection against marine organisms and microorganisms.
Patent Information
- Application Number
- CN202310983969.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-08-07
AI Technical Summary
The existing zwitterionic polymer coatings have problems such as insufficient anti-fouling stability, insufficient mechanical strength and easy dissolution in the marine environment, making it difficult to effectively prevent pollution and corrosion for a long time.
A amphiphilic conductive polymer coating is prepared by copolymerizing conductive polymer monomers modified with zwitterionic and hydrophobic groups using conductive polymer materials as the main chain. This coating improves mechanical strength and antifouling properties by forming a dense hydrating layer and enhanced hydrophobic groups.
It realizes effective anti-adhesion and corrosion resistance to marine organisms and microorganisms, improves the mechanical strength and long-term anti-fouling stability of the coating, and is suitable for long-term applications in marine environments.
Smart Images

Figure SMS_1 
Figure SMS_19 
Figure SMS_20
Abstract
Description
Technical Field
[0001] The invention relates to an amphiphilic coating based on conductive polymer with high mechanical strength, which is applied in the field of marine antifouling and anticorrosion. Background Art
[0002] The ocean accounts for more than 70% of the earth's surface area and contains inestimable resources. The ocean has become an inevitable choice and important space for my country's economic and social development. However, in the process of developing and utilizing marine resources, ships, marine water and underwater facilities, etc. generally face the problems of marine biofouling and marine corrosion in long-term applications. The accumulation of fouling organisms on the surface of the hull will increase the surface roughness, leading to increased friction resistance and fuel consumption. In addition, underwater facilities are also faced with corrosion problems, including seawater corrosion and microbial corrosion. Seawater is a corrosive substance, rich in oxygen and ions, which will react electrochemically with the metal surface, resulting in corrosion. Microbial corrosion is the local change of dissolved oxygen, redox potential and pH value caused by the deposition of microorganisms on the surface, which enhances the chemical / electrochemical reaction between microorganisms, media and metals, leading to or accelerating the corrosion of metal surfaces. At the same time, studies have found that biofouling and marine corrosion promote each other. Biofouling promotes the corrosion of the metal substrate, and marine corrosion is more likely to occur on the rough surface of biofouling. Therefore, it is urgent to develop and design marine antifouling and anticorrosion coatings with excellent performance.
[0003] In recent years, zwitterionic polymers have made certain research progress by forming a dense hydration layer, which can effectively inhibit biofouling and microbial corrosion, and have great potential in the field of marine antifouling. Chinese patent CN107312122 discloses the random copolymerization of dopamine methacrylamide monomer (DMA) and methacryloylethyl sulfobetaine monomer (SB) into polydopamine methacrylamide sulfobetaine (PDMASB), which exhibits good antifouling performance. Chinese patent CN112194767 discloses a sulfobetaine functionalized benzoxazine resin, and the cross-linked polybenzoxazine coating containing zwitterionic groups has good antifouling performance and reduces protein adhesion by 98%. However, the superhydrophilic surface formed by zwitterionic polymers will promote the penetration of ions and seawater, making it difficult to resist the corrosion of seawater and accelerate the corrosion of metal substrates. In addition, biological fouling will further occur on the corroded surface, so it is urgent to improve the corrosion resistance of the coating. In addition, due to the super hydrophilicity of zwitterionic polymers, they are easily dissolved in water, and their mechanical strength is insufficient. At the same time, they are affected by the harsh underwater environment, making their antifouling effect ineffective. Therefore, it is necessary to improve the mechanical strength of zwitterionic polymer coatings so that they can maintain long-term antifouling stability. Therefore, preparing a marine antifouling and anticorrosive coating with long-term antifouling stability has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the existing technical problems, the present invention aims to prepare a new coating to overcome the deficiencies of the prior art, and provides a new type of antifouling and anticorrosion coating. The antifouling and anticorrosion coating of the present invention is a marine antifouling and anticorrosion coating with excellent long-term antifouling stability. A large number of studies have shown that zwitterions can form a dense hydration layer with water molecules, provide a physical and energy barrier, effectively prevent the adhesion of proteins and microorganisms, and have great potential as an anti-biological fouling material. In order to solve the problem of corrosion of metal substrates, inspired by the special electrochemical properties of conductive polymers, conductive polymers can act as a barrier to hinder the penetration of ions into the substrate, and at the same time, their excellent ability to conduct electrons and ions can promote the delocalization of surface charges, avoid the formation of local anode or cathode regions and produce local corrosion. With conductive polymers as the main chain, chemically modified zwitterionic groups are constructed, and it is expected to achieve antifouling and anticorrosion effects. In addition, in view of the insufficient antifouling stability of the coating, hydrophobic groups are modified on the main chain of the conductive polymer, and the hydrophobic groups can enhance the mechanical properties of the coating, so that the coating can remain stable in the marine environment, thereby obtaining excellent long-term antifouling stability.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] An anti-fouling and anti-corrosion conductive polymer material has groups that can resist the adhesion of proteins, microorganisms and bacteria.
[0007] The antifouling and anticorrosive conductive polymer material preferably has a hydrophobic group that provides mechanical strength and improves the antifouling performance.
[0008] Preferably, the conductive polymer structure general formula (I) of the anti-fouling and anti-corrosion conductive polymer material is:
[0009]
[0010] in:
[0011] for Any of the following:
[0012] -R1 is Any one of , where c is a positive integer and 1≤c≤10;
[0013] -R2 is -C4H9, -C6H 13 、-C8H 17 , -C 10 H 21 , -C 12 H 25 、-C4F9、-C6F 13 、-C8F17 , C 10 F 21 or -C 12 F 25 Any of the following:
[0014] m, n are positive integers, and 0≤m≤5000, 0≤n≤5000;
[0015] -L1- is -(CH2) x -、-(CH2) x -O-(CH2) y -、-(CH2) x -O-CO-(CH2) y -、-(CH2) x -(CH2-CH2-O) y -、-(CH2) x -O-(CH2-CH2-O) y -、-O-(CH2) x -(CH2-CH2-O) y -or-O-(CH2) x -O-(CH2-CH2-O) y Any one of , wherein x, y are integers, and 0≤x≤5, 0≤y≤5;
[0016] -L2- is -(CH2) x -、-O-(CH2) x -、-C(O)-O-(CH2) x -、-C(O)-NH-(CH2) x -、-C(CH3)2-C(O)-O-(CH2) x -、-CH(CH3)-O-(CH2) x -、-S-CH2-CH2-O-(CH2) x -or-S-CH2-CH(CH3)-C(O)-O-(CH2) x -, wherein x is an integer and 0≤x≤5;
[0017] Preferably, considering the convenience of raw material preparation, for Any one of .
[0018] Preferably, -R1 is Any one of , where c is a positive integer and 1≤c≤5.
[0019] Preferably, -R2 is -C4H9, -C6H 13 、-C8H17 、-C4F9、-C6F 13 、-C8F 17 Any one of .
[0020] Preferably, in the general structural formula (I), m:n is 10:100 to 10:100, and m+n=100.
[0021] Preferably, considering the effect of the alkylene chain length on the solubility of the polymer, -L1- is -(CH2) x -、-(CH2) x -O-(CH2) y Any one of, wherein x, y are integers, and 0≤x≤5, 0≤y≤5; -L2- is -(CH2) x -、-O-(CH2) x -, wherein x is an integer and 0≤x≤5.
[0022] The invention prepares an amphiphilic conductive polymer coating with certain mechanical strength and excellent antifouling performance by copolymerizing a zwitterionic group-modified conductive polymer monomer and a hydrophobic group-modified conductive polymer monomer, and has wide applications and high application prospects.
[0023] Compared with the prior art, the present invention has the following obvious outstanding substantive features and significant advantages:
[0024] The antifouling and anticorrosive conductive polymer material of the present invention modifies the conductive polymer with zwitterions so that the coating can resist the adhesion of marine organisms such as proteins, diatoms, mussels, etc., and has an anti-corrosion effect; by introducing a hydrophobic structure on the main chain of the conductive polymer, the mechanical strength of the coating can be improved, thereby maintaining its long-term antifouling stability, which is crucial for its application in the ocean. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The anti-fluorescent protein adhesion performance of the anti-fouling and anti-corrosion coatings of Examples 1, 2, 3 of the present invention and Comparative Example 1 before and after being immersed in mud and sand for two weeks;
[0026] Figure 2 The anti-diatom adhesion performance of the anti-fouling and anti-corrosion conductive polymer coating of Example 4 of the present invention for two weeks;
[0027] Figure 3 The anti-diatom adhesion performance of the anti-fouling and anti-corrosion conductive polymer coating of Example 5 of the present invention for two weeks;
[0028] Figure 4 The anti-diatom adhesion performance of the anti-fouling and anti-corrosion conductive polymer coating of Example 6 of the present invention for two weeks;
[0029] Figure 5 Corrosion polarization curves of the antifouling and anticorrosion conductive polymer coatings of Examples 7, 8, and 9 of the present invention;
[0030] Figure 6 The anti-protein adhesion effect of the anti-fouling and anti-corrosion conductive polymer coating of Example 10 of the present invention and Comparative Example 3;
[0031] Figure 7 These are the corrosion polarization curves of the antifouling and anticorrosion conductive polymer coatings of Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:
[0033] Embodiment 1:
[0034] In this embodiment, the structure of an antifouling and anticorrosive conductive polymer coating includes 16.8 mg of Conductive monomer I-1 (0.05 mmol) containing a -C4H9 group and 34.2 mg of conductive monomer II-1 (0.15 mmol) containing a -C4H9 group were copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-1, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. The long-term anti-fouling stability of the anti-fouling and anti-corrosion coating was tested using the anti-fluorescent protein test before and after mud and sand immersion, with the fluorescent BSA protein as the model. The results are shown in Table 1. Figure 1 As shown; the corrosion resistance of the antifouling and anticorrosion coating was tested using electrochemical technology. The corrosion potential was -0.14V and the corrosion current was 3.55E-6A. The results are shown in Figure 7 shown.
[0035] Embodiment 2:
[0036] In this embodiment, the structure of an antifouling and anticorrosive conductive polymer coating includes 16.8 mg of Conductive monomer Ⅰ-2 (0.05 mmol), 12.8 mg containing -C6H 13 Conductive monomer II-2 (0.05 mmol) of the group was copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-2, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. The long-term anti-fouling stability of the anti-fouling and anti-corrosion coating was tested by using the anti-fluorescent protein test before and after mud and sand immersion, using the fluorescent BSA protein as a model. The results are shown in Figure 1. Figure 1 shown.
[0037] Embodiment 3:
[0038] In this embodiment, the structure of an antifouling and anticorrosive conductive polymer coating comprises 50.5 mg of Conductive monomer Ⅰ-3 (0.15 mmol), 14.2 mg containing -C8H 17 Conductive monomer II-3 (0.05 mmol) of the group was copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-3, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. The long-term anti-fouling stability of the anti-fouling and anti-corrosion coating was tested using the fluorescent BSA protein as a model using the anti-fluorescent protein test before and after mud and sand immersion. The results are shown in Figure 1. Figure 1 shown.
[0039] Embodiment 4:
[0040] In this embodiment, a structure of an antifouling and anticorrosive conductive polymer coating comprises 17.2 mg of Conductive monomer Ⅰ-4 (0.06 mmol), 35.6 mg containing -C 10 H 21 Conductive monomer II-4 (0.14 mmol) of the group was copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-4, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. The anti-fouling performance of the anti-fouling and anti-corrosion coating was tested using a diatom adhesion test for two weeks, and the average static diatom adhesion amount was 10.2 / cm 2 The results are as follows Figure 2 shown.
[0041] Embodiment 5:
[0042] In this embodiment, a structure of an antifouling and anticorrosive conductive polymer coating comprises 14.5 mg of Conductive monomer Ⅰ-5 (0.05 mmol), 14.6 mg -C 12 H 25 Conductive monomer II-5 (0.05 mmol) of the group was copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-5, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. The anti-fouling performance of the anti-fouling and anti-corrosion coating was tested by diatom adhesion test for two weeks, and the average static diatom adhesion amount was 7.4 / cm 2 The results are as follows Figure 3 shown.
[0043] Embodiment 6:
[0044] In this embodiment, a structure of an antifouling and anticorrosive conductive polymer coating comprises 54.8 mg of 21.6mg of conductive monomer I-6 containing -C4F9 group (0.20mmol) and 21.6mg of conductive monomer II-6 containing -C4F9 group (0.05mmol) were copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-6, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. The anti-fouling performance of the anti-fouling and anti-corrosion coating was tested by diatom adhesion test for two weeks, and the average static diatom adhesion amount was 4.6 / cm 2 The results are as follows Figure 4 shown.
[0045] Embodiment 7:
[0046] In this embodiment, the structure of an antifouling and anticorrosive conductive polymer coating includes 12.7 mg of Conductive monomer Ⅰ-7 (0.05 mmol), 62.4 mg containing -C6H 13 Conductive monomer II-7 (0.15 mmol) of the group was copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-7, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. The corrosion resistance of the anti-fouling and anti-corrosion coating was tested using electrochemical technology. The corrosion potential was -0.07 V and the corrosion current was 1.14E-6 A. The results are shown in Table 1. Figure 5 shown.
[0047] Embodiment 8:
[0048] In this embodiment, a structure of an antifouling and anticorrosive conductive polymer coating comprises 25.9 mg of Conductive monomer Ⅰ-8 (0.09 mmol), 59.5 mg containing -C8F 17 Conductive monomer II-8 (0.11 mmol) of the group was copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-8, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. Using electrochemical technology, the corrosion potential is -0.03V and the corrosion current is 3.27E-7A. The corrosion resistance of the anti-fouling and anti-corrosion coating is tested. The results are shown in Figure 5 shown.
[0049] Embodiment 9:
[0050] In this embodiment, a structure of an antifouling and anticorrosive conductive polymer coating comprises 54.4 mg of Conductive monomer Ⅰ-9 (0.2 mmol), 35.9 mg -C 10 H 21Conductive monomer II-9 (0.05 mmol) of the group was copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-9, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this embodiment are shown in Table 1. The corrosion resistance of the anti-fouling and anti-corrosion coating was tested using electrochemical technology. The corrosion potential was -0.002 V and the corrosion current was 3.39E-7 A. The results are shown in Figure 1. Figure 5 shown.
[0051] Embodiment 10:
[0052] In this embodiment, a structure of an antifouling and anticorrosive conductive polymer coating comprises 40.7 mg of Conductive monomer Ⅰ-10 (0.14 mmol), 44.6 mg containing -C 12 H 25 Conductive monomer II-10 (0.06 mmol) of the group was copolymerized and deposited on the surface of 316L stainless steel to obtain conductive polymer III-10, which is the desired anti-corrosion and anti-fouling conductive polymer coating. The conductive polymer monomer materials and proportions used in this example are shown in Table 1. The anti-fouling performance of the anti-fouling and anti-corrosion coating was tested using QCM technology with BSA protein as a model. The frequency of the drop was 8 Hz. The results are shown in Figure 6 shown.
[0053] The preferred comparative examples of the present invention are described in detail as follows:
[0054] Comparative Example 1:
[0055] In this comparative example, the structure of an antifouling and anticorrosion coating includes 16.8 mg of monomer Ⅰ-1 (0.05 mmol), which is polymerized and deposited on the surface of 316L stainless steel to obtain polymer Ⅲ-1, which is the desired anticorrosion and antifouling coating. The polymer monomer materials and proportions used in this comparative example are shown in Table 2. Using the anti-fluorescent protein test before and after mud and sand immersion, the fluorescent BSA protein is used as a model to compare it with the long-term antifouling stability of the antifouling and anticorrosion conductive polymer coating. The results are shown in Figure 2. Figure 1 Shown
[0056] Comparative Example 2:
[0057] In this comparative example, the structure of an antifouling and anticorrosion coating includes 16.2 mg of monomer Ⅰ-2 (0.05 mmol), which is polymerized and deposited on the surface of 316L stainless steel to obtain polymer Ⅲ-2, which is the desired anticorrosion and antifouling coating. The polymer monomer materials and proportions used in this comparative example are shown in Table 2. Using electrochemical technology, it is compared with the corrosion resistance of the antifouling and anticorrosion conductive polymer coating. The corrosion potential is -0.21V and the corrosion current is 9.46E-6A. The results are as follows: Figure 7 shown.
[0058] Comparative Example 3:
[0059] In this comparative example, the structure of an antifouling and anticorrosion coating includes 7.1 mg of monomer I-3 (0.05 mmol), which is polymerized and deposited on the surface of 316L stainless steel to obtain polymer III-3, which is the desired anticorrosion and antifouling coating. The polymer monomer materials and proportions used in this comparative example are shown in Table 2. Using QCM technology, BSA protein is used as a model to compare its antifouling performance with that of the antifouling and anticorrosion conductive polymer coating. The frequency of the drop is 17.9 Hz, and the results are as follows Figure 6 shown.
[0060] From the above examples and comparative examples, it can be seen that the conductive polymer monomer materials and ratios used in Examples 1-9 are shown in Table 1, and the polymer monomer materials and ratios used in Comparative Examples 1-3 are shown in Table 2.
[0061] Table 1. Material information table used in Examples 1-10 of the present invention
[0062]
[0063]
[0064]
[0065] Table 2. Material information table of comparative examples 1-3 of the present invention
[0066]
[0067] Based on the above Table 1 and Examples 1-10 of the present invention, it can be known that different conductive monomers containing hydrophobic groups and conductive monomers containing zwitterionic groups can be deposited and polymerized on a substrate to obtain various antifouling and anticorrosion conductive polymer coatings; the above embodiment method prepares an amphiphilic marine antifouling and anticorrosion coating with long-term antifouling stability by copolymerizing zwitterionic group-modified conductive polymer monomers and hydrophobic group-modified conductive polymer monomers, which has a wide range of uses and high application prospects. The anticorrosion and antifouling conductive polymer coating of the present invention modifies the conductive polymer with zwitterionic groups to obtain excellent dynamic and static anti-adhesion properties to marine organisms such as microorganisms, marine animals and plants, and has anticorrosion properties; by modifying the hydrophobic group on the main chain of the conductive polymer, the coating can provide certain mechanical properties and improve its antifouling stability.
[0068] The above describes the embodiments of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention and do not deviate from the technical principles and inventive concepts of the anti-fouling and anti-corrosion conductive polymer material and the preparation method thereof, they belong to the protection scope of the present invention.
Claims
1. An anti-fouling and anti-corrosion conductive polymer material, characterized in that A random copolymer having a hydrophilic group and a hydrophobic group, wherein the general structural formula (I) of the copolymer is: in: for Any of the following; -R1 is Any one of , where c is a positive integer and 1≤c≤10; -R2 is -C4H9, -C6H 13 、-C8H 17 , -C 10 H 21 , -C 12 H 25 、-C4F9、-C6F 13 、-C8F 17 , -C 10 F 21 or -C 12 F 25 Any of the following; m, n are positive integers, and 0≤m≤5000, 0≤n≤5000; -L1- is -(CH2) x -、-(CH2) x -O-(CH2) y -、-(CH2) x -O-CO-(CH2) y -、-(CH2) x -(CH2-CH2-O) y -、-(CH2) x -O-(CH2-CH2-O) y -、-O-(CH2) x -(CH2-CH2-O) y -or-O-(CH2) x -O-(CH2-CH2-O) y Any one of , wherein x, y are integers, and 0≤x≤5, 0≤y≤5; -L2- is -(CH2) x -、-O-(CH2) x -、-C(O)-O-(CH2) x -、-C(O)-NH-(CH2) x -、-C(CH3)2-C(O)-O-(CH2) x -、-CH(CH3)-O-(CH2) x -、-S-CH2-CH2-O-(CH2) x -or-S-CH2-CH(CH3)-C(O)-O-(CH2) x -, wherein x is an integer and 0≤x≤5.
2. A conductive polymer material according to claim 1, and for Any one of .
3. A conductive polymer material according to claim 1, -R1 is Any one of , where c is a positive integer and 1≤c≤5.
4. The conductive polymer material according to claim 1, wherein -R2 is -C4H9, -C6H 13 、-C8H 17 、-C4F9、-C6F 13 、-C8F 17 Any one of .
5. A conductive polymer material according to claim 1, wherein in the general structural formula (I), m:n is 10:100 to 100:10, and m+n=100.
6. The conductive polymer material according to claim 1, wherein -L1- is -(CH2) x -、-(CH2) x -O-(CH2) y Any one of x, y are integers, and 0≤x≤5, 0≤y≤5; -L2- is -(CH2) x -、-O-(CH2) x -, wherein x is an integer and 0≤x≤5.
Citation Information
Patent Citations
Anti-drag and anti-fouling paint for water tunnels of offshore power plants and preparation method thereof
CN107141942A
Surface anticorrosive antifouling coating using polydopamine as base layer as well as modification method and application of coating
CN110643277A